Post caesarean section outcomes of obstetric valvular heart disease patients at Charlotte Maxeke Johannesburg Academic Hospital - Mfeka, Ntombizabanguni Glory (University of the Witwatersrand, Johannesburg, 2022)
Background Valvular heart disease presents a unique set of conditions during pregnancy and delivery with the potential of adverse outcomes complicated by prior interventions and anticoagulation. The aim of this study was to describe the profile and outcomes of obstetric valvular heart disease patients who delivered via caesarean section at Charlotte Maxeke Johannesburg Academic Hospital. Methods A retrospective study was done using patient record files, anaesthetics forms and echocardiogram reports. The study period was a 5-year review from January 2016 to December 2020. Results Sixty-nine patients were included. The mean age ± SD of the patients in this study was 30.1 ± 5.6 years. A total of 83% had gravidity of 1-3 and 90% parity of 0-2. Majority of patients (57%) had elective caesarean section. General anaesthesia was the most common mode used and majority of patients had fixed interval analgesia (FIA) mode of analgesia postoperatively. 40.5% of the patients were on anticoagulants. A significantly higher percentage of those who needed anticoagulation (46%) had poorer outcomes when compared to those who did not (7%), (P<0.001). The was a univariable association between adverse maternal outcome and NYHA class and lack of use of anticoagulants [aOR 3.77, 95%CI 1.45 – 9.79, P=0.006 and aOR 0.11, 95%CI 0.018 – 0.67, P=0.017, respectively]. Low ejection fraction was univariably associated with adverse foetal outcome, uOR 0.94, 95%CI 0.90 – 0.99, P=0.032. One (1%) foetus demised. Conclusion Patients were younger and in relatively good functional status. They carried the pregnancies to term. Patients did experience adverse outcome related to bleeding and arrythmias predominantly, but none demised. One neonate was lost. A structured care plan for these patients, based on a multidisciplinary approach, to afford prehabilitation is necess
A research report submitted in partial fulfillment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology to the faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2022
Keywords: Obstetric valvular heart disease; Caesarean section; Adverse outcomes; UCTD; SDG-3: Good health and well-being